Analisis Dan Perancangan Sistem Informasi Jual Beli Motor Murah Agus Motor - I Gede Agus Rudaya; Mikail Abdullah; Leon Farrel Agung Permana; Richard Andrean; Putu Alva Ananda Shakira; Ary Putra Sanjaya (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2022)
An information system is a system within an organization that brings together daily transaction processing needs that support managerial organizational functions in strategic activities of an organization to be able to provide certain outside parties with the reports needed. The company can be said to be a unit in a system. which influence each other, to achieve a goal. But sometimes in achieving these goals, several obstacles are often found, including data processing that is still done manually, and the increasing number of transactions every year. In running its business, the owner of AGUS MOTOR performs all its business activities manually, both recording sales and purchases data, searching for sales and purchase data, and in recapitulating income and expenditure data. Based on these problems, a motorcycle showroom information system is needed. Building an information system, requires analysis of requirements and system design, so that the system implemented is in accordance with user needs. The purpose of this research is to model business processes, analyze requirements specifications and system design, and evaluate requirements specifications and system interface designs. This study uses BPMN to model business processes and in this problem is described by UML (Unified Modeling Language). computerized and the resulting information can meet the needs of users as system users.